Projected Individual Water Needs of Israeli Settlers in 2025 :The Impact on Water Security of the Palestinians - Abu Zaher نادية (Journal of King Abdulaziz University: Environmental Design Sciences, 2021)
This study looks into the impact of the projected individual water needs of Israeli settlers in the West Bank in 2025 on water security of the Palestinians of the same area. The study utilizes the ’Time Series’ approach, which is based on several indicators, including UN indicators which estimate individual water needs for drinking, cooking, and cleaning. The study concluded that the percentage of Palestinian to settlers in the West Bank is steadily decreasing. In 1982, the Palestinians constituted 82% of the population of the West Bank. By 2025, the projected percentage is 72%. The Palestinian population in 2025 is expected to be about 3.5 million, while the number of settlers will exceed half a million, i.e., 14.5% of the total. The settlers’ consumption will be equivalent to 63.3% of the Palestinians’ consumption. In other words, the consumption of half a million settlers will be an equivalent to that of 2.2 million Palestinians. By 2025, this increasing of the Israeli population’s percentage in the West Bank will lead to a high level of water consumption by the settlers 42% for the settlers, and 58% for the Palestinians. The projected individual water needs of Israeli settlers will have a harmful impact on the steadily decreasing of the Palestinians amounts of water, and their projected individual water needs. This will have a harmful impact on their water security. This will mean less water for the Palestinians to meet their basic needs. Moreover, If this trend continues, it is conceivable that the number of settlers in the West Bank will become equal to the Palestinians. This will not only undermine the Palestinians’ water security; it will also usurp their right to a Palestinian state.